3 Year Longıtudınal Changes In Cephalometrıc Skeletal Measurements Of Young Adults - Aslı Ender Telli; Bülent Haydar; Pınar Saatçi (Galenos Yayinevi, 1995)
26 female and 24 male patients with an avarage chronological age of 18.96±132 years were selected in order to evaluate the skeletal changes in young adults. The lateral cephalometric radiographs were obtained at natural head position and 17 angular, 6 linear measurements were done. The same measurements were repeated after three years of observation and student t test was used to evaluate the mean differences between the two groups. In young male adults an increase in posterior cranial base height and a decrease in ANB angle was observed. In young female adults upper, and lower incisors inclined labially and a decrease was observed in interincisal SNA, SNB and gonial angles.